2001
DOI: 10.1097/00006842-200109000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Self-Efficacy as a Predictor of Adult Adjustment to Sickle Cell Disease: One-Year Outcomes

Abstract: Self-efficacy beliefs among African American adults with sickle cell disease are inversely related to reported disease symptomatology, and these relationships persist across time. Future investigations should examine the mechanisms through which relationships between self-efficacy and adjustment to sickle cell disease are effected, as well as the feasibility and effectiveness of enhancing self-efficacy beliefs as a means of improving adjustment to sickle cell disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
70
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(80 citation statements)
references
References 54 publications
7
70
0
3
Order By: Relevance
“…These studies indicate that high levels of self-efficacy in aspects of physical functioning are associated with higher quality of life, lower levels of depression, and higher functioning in everyday activities. Similarly, studies examining the role that selfefficacy plays in adjustment to chronic illnesses [22][23][24][50][51][52] have also found that high levels of self-efficacy contributed to better coping and reduced symptoms in individuals living with a chronic medical condition.…”
Section: Discussionmentioning
confidence: 99%
“…These studies indicate that high levels of self-efficacy in aspects of physical functioning are associated with higher quality of life, lower levels of depression, and higher functioning in everyday activities. Similarly, studies examining the role that selfefficacy plays in adjustment to chronic illnesses [22][23][24][50][51][52] have also found that high levels of self-efficacy contributed to better coping and reduced symptoms in individuals living with a chronic medical condition.…”
Section: Discussionmentioning
confidence: 99%
“…Learning to control disease symptoms provides a means to increase disease self-efficacy and more confidently manage disease. In a review of the literature, Edwards and colleagues emphasize that separate studies have positively linked the role of selfefficacy to adjustment in several chronic conditions such as fibromyalgia, arthritis, chronic low back pain, diabetes, cystic fibrosis, multiple sclerosis, and chronic obstructive pulmonary disease (Edwards, Telfair, Cecil, & Lenoci, 2001). …”
Section: Chronic Illness Self-efficacy and The Conceptual Basis Of mentioning
confidence: 99%
“…After developing the first disease-specific self-efficacy measure for SCD, Edwards and colleagues demonstrated in 147 African American adults with SCD that self-efficacy was inversely related (p b .01) to physical and psychological symptoms, pain severity and number of physician visits in the preceding 12 months. In a 1-year follow-up of these patients, changes in self-efficacy were significantly and independently related to changes in physical symptoms, psychological symptoms, and pain ratings (Edwards et al, 2001). One study examined the relationship of self-efficacy to illness uncertainty and self-care in 85 adult patients with SCD recruited from three hospitals in the United States.…”
Section: Chronic Illness Self-efficacy and The Conceptual Basis Of mentioning
confidence: 99%
See 1 more Smart Citation
“…About 8% of Afro-Americans possess the trait (Neel, 1949). This inherited blood disease affects approximately 50,000-65,000 individuals, generally of African descent, in the United States (Edwards et al, 2004). In several sections of Africa, the prevalence of sickle-cell trait (heterozygote) is as high as 30%, and in places where malaria is prevalent, the population is 40% heterozygous for SCA (Serjeant, 1994).…”
Section: Introductionmentioning
confidence: 99%